2010
DOI: 10.1080/02687038.2010.500810
|View full text |Cite
|
Sign up to set email alerts
|

Divergences of perspective between people with aphasia and their family caregivers

Abstract: LSE has developed LSE Research Online so that users may access research output of the School. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LSE Research Online to facilitate their private study or for non-commercial research. You may not engage in further distribution of the material or use it for any profit-making activities or any commercial gain. You may freely distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 36 publications
(34 reference statements)
0
34
0
1
Order By: Relevance
“…• Using the Talking Mats™ framework with both members of dyads is recommended in a clinical setting (Gillespie et al, 2010). The use of Talking • Ideally, the process of selecting relevant topics for inclusion in an AAC system should involve time, thought and input from various informants (Garrett et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Using the Talking Mats™ framework with both members of dyads is recommended in a clinical setting (Gillespie et al, 2010). The use of Talking • Ideally, the process of selecting relevant topics for inclusion in an AAC system should involve time, thought and input from various informants (Garrett et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used successfully with people with dementia, intellectual disabilities and aphasia (Murphy et al, 2007;Murphy & Cameron, 2008;Brewster, 2004;Murphy, 2000;Gillespie, et al, 2010). Talking Mats™ was therefore selected as the method in which to assist the participants with aphasia to evaluate the conversational topics in this study.…”
Section: Talking Mats™mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond using assistive technologies, people with aphasia often receive day-to-day help from an informal carer (usually a family member). Research has revealed a wide range of misunderstandings between informal care givers and receivers in both aphasia and other disabilities (Gillespie et al, 2010). For example, it is common for care receivers to underestimate the effort and distress of the main carer.…”
Section: (2) Informal Care For People With Aphasiamentioning
confidence: 99%
“…Gillespie and colleagues have examined the dynamics of dialogue in studies of people with aphasia and their main informal carers (Gillespie et al, 2010). Aphasia is a communication difficulty, often caused by stroke or trauma, which affects speaking, understanding, reading and/or writing.…”
Section: (2) Informal Care For People With Aphasiamentioning
confidence: 99%